Will China split Taiwan? After the passing of the "Anti-Secession Law" - Kay Moeller (Stiftung Wissenschaft und Politik (SWP), 2005)
By passing an 'Anti-Secession Law' in March 2005, China's National People's Congress could have contributed to a further polarization of Taiwan's political landscape. In late March, the island's main opposition party made an attempt to wrench back the initiative on mainland policy by negotiating a broadening of economic and other relations in Peking. In Taipei, the administration of Taiwan's president, Chen Shuibian, castigated the initiative as a sellout of national interests and launched a review of the entire economic relationship with the People's Republic of China (PRC). Both the government and the opposition are running considerable risks with a Taiwanese population that is at the same time opposed to the 'Anti-Secession Law' and supportive of a decrease in tensions across the Taiwan Strait. (SWP Comments / SWP)
Keywords: 320